Analisis Sumber Belajar Dan Bahan Ajar Dalam Pembelajaran IPA Di SD Negeri 106161 Laut Dendang - Fenny Rizky Amelia; Renni Lumban Gaol; Indah Aprilia; Elisabeth Kezia Tampubolon; Nazwa Audina Br Manurung; Hiskia Julius Renata Gultom (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2025)
Basic school science learning requires a variety of learning resources and relevant teaching materials to improve students' understanding and interest. This study aims to analyze the use of learning sources and teaching materials in science lessons at SDN 106161 Laut Dendang. The method used is a descriptive qualitative approach, through questionnaires and interviews with 23 students and teachers. The results show that diverse sources and hands-on activities enhance students’ understanding and motivation. In conclusion, developing contextual materials and providing teacher training are crucial for more effective and meaningful science learning.